Child Negative Emotionality and Parental Harsh Discipline in Chinese Preschoolers: The Different Mediating Roles of Maternal and Paternal Anxiety - Xing, Xiaopei; Zhang, Hongli; Shao, Shuhui; Wang, Meifang (Frontiers in Psychology, 2017)
Previous research has suggested that harsh discipline is still prevalent in modern Chinese families and it is necessary to explore the cause and the potential mechanisms of Chinese parental use of harsh discipline. This study examined the mediating effects of parental anxiety in the relations between child negative emotionality and parental harsh discipline in China. Using a sample of 328 Chinese father-mother dyads with their young children, findings revealed that maternal anxiety mediated the relations between child negative emotionality and maternal psychological aggression and corporal punishment, but the mediating effects of paternal anxiety on the relations between child negative emotionality and paternal harsh discipline was not significant. The findings provide an important supplement and extension to previous examinations of the factors associated with Chinese parental use of harsh discipline and its mechanisms.